Green Process for the Enzymatic Synthesis of Aroma Compounds Mediated by Lipases Entrapped in Tailored Sol–Gel Matrices - Adrian Ioan Dudu (10531989); Mihai Andrei Lăcătuş (10531992); László Csaba Bencze (8282154); Csaba Paizs (514921); Monica Ioana Toşa (8282160) (2021)
We report a simple enzymatic procedure for the synthesis of short-chained flavor esters by direct esterification of natural acids with short-chain primary alcohols mediated by lipase B from Candida antarctica entrapped in a tailored sol–gel matrix in the presence of three additives, using vacuum for water removal. Maximal immobilization yields (100%) were obtained for all three biocatalysts, while the enzyme loading and the synthetic activity depend on the used additive (6.7, 7.6, and 7.7 μg enzyme/mg biocatalyst for β-cyclodextrin, polyvinyl alcohol, and glycerol, respectively, and 76–110% recovered activity as compared with free lipase). The process was optimized using the reaction of hexan-1-ol with butyric acid as the model with significant conversion improvements (from <40% to >94%) reducing the alcohol/enzyme ratio (from 100:1 to 25:1 weight ratio) for all novel biocatalysts. Other short-chain flavor esters were prepared with excellent yields (>90%) under the previously established optimal conditions. Atom economy (90.53), E -factor (17.22), atom efficiency (88.36), mass intensity (18.58), and reaction mass efficiency (60.07) as relevant sustainability metrics were calculated for the preparative scale model reaction with glycerol as the additive. Based on our results, this green and sustainable new approach can be used for the synthesis of many flavor esters.